Chickpea (Cicer arietinum L.) sprouts containing supranutritional levels of selenium decrease tumor growth of colon cancer cells xenografted in immune-suppressed mice. (February 2019) - Guardado-Félix, Daniela; Antunes-Ricardo, Marilena; Rocha-Pizaña, María R.; Martínez-Torres, Ana-Carolina; Gutiérrez-Uribe, Janet A.; Serna Saldivar, Sergio O.
Graphical abstract: Highlights: Selenium enriched chickpea sprouts decreased colorectal cancer (CRC) tumor growth in vivo . High selenium contained in the diets increased GPx activity. CHOL, TRIGL and LDL levels were closer to the basal in the groups receiving selenized diets. Selenized chickpea sprouts promoted apoptosis by overexpression of Fas protein. Abstract: The effect of selenium enriched chickpea sprouts with and without isoflavonoids (IS) on colorectal cancer (CRC) tumor growth was evaluated in immune-suppressed mice xenografted. Two levels of selenium (0.17 and 2.29 µg/g) and isoflavonoids (0 and 2.34 mg/g) were evaluated in the diets. High intake of Se (2.29 µg/g) with and without isoflavonoids increased glutathione peroxidase (GPx) and tioredoxin reductase (TrxR) activities, cholesterol (CHOL), triglycerides (TRIGL) and low-density lipoprotein cholesterol (LDL-C) levels and decreased significantly the tumor growth. Diet containing selenium at 2.29 µg/g and isoflavonoids at 2.34 mg/g levels promoted apoptosis through the overexpression of Fas cell surface death receptor (Fas). High selenium levels in chickpea sprouts exert chemopreventive effects mediated mainly by the antioxidant protection of glutathione peroxidase. Selenized chickpea sprouts represent an excellent source of dietary selenium and isoflavonoids with chemopreventive potential and could be potentially used in the treatment of colorectal cancer.